How the mighty fall - Baden-Powell, Edwina; Garner, Simon; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2004)
This program examines three case studies of corporate collapses in Australia around the turn of the 21st century. They are HIH - at the time, the biggest corporate collapse in Australia's history; One.Tel; and Waterwheel Holdings.
Title from title screen
Executive producer, Mark McAuliffe ; editor, Adrian Vallis
DVD format
Keywords: HIH Insurance; One.Tel (Firm); Waterwheel Holdings; Business failures -- Australia -- Case studies